THE EFFECT OF WORK FAMILY CONFLICT, JOB STRESS, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Widayati, C. Catur; Arijanto, Agus; Magita, Magita; Anggraini, Wahyu; Putri A, Adinda (Dinasti Publisher, 2021)
This study aims to analyze the effect of work-family conflict, work stress, and job satisfaction on employee performance. The population in this study was 70 employees at a pension fund company. The sampling method used is a saturated sample, so that the sample used is 70 employees. Data collection methods using survey methods, with the research instrument is a questionnaire—data analysis method using Partial Least Square. The findings in this study prove that: 1) Work-Family Conflict has a negative and significant effect on employee performance; 2) Job stress has a negative and significant effect on employee performance; 3) Job satisfaction has a positive and significant effect on employee performance.